THE CONCEPT OF SELF-DETERMINATION IN THE PHILOSOPHY OF THE ENLIGHTENMENT - V. V. Khmil; O. M. Korkh (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The purpose of the article is to define main directions and ways to legitimize philosophical ideas of self-determination as a fundamental global and valuable intention of Western culture in the context of its enlightenment paradigm. Methodology. The research is based on historical and logical methods, which allowed to theoretically reconstruct the cultural and historical context, as well as philosophical and theoretical principles of understanding and recognition of self-determination as a phenomenon of Western culture of the Enlightenment age. The authors have used their own theoretical model similar to the one of “ideal type” by. M.Weber based on the methods of generalization, abstraction and idealization, which allowed to present the phenomenon of individualism in the most general form as a system of value orientations of an individual, whose nature is seeking self-determination and originality. Originality. The historical and philosophical analysis has shoяк.wn how the philosophy of the Enlightenment age created moral principles of European culture advancement, especially through rationalization and the idea of political, economic and moral independence of a personality, recognition of rights for own initiative and sovereignty, individual identity as a public good. Thus, the idea of self-determination in this philosophy is related not only to the recognition of human rights, but also to the search of possible ways for a person to embrace current legislative system, harmony conditions and public interests. Conclusions. The philosophy of the Enlightenment has made a significant step toward further development of self-determination concept and its rationalization – separation of freedom and tyranny, new perception of necessary conditions for free self-determination of an individual as the ability to manage own passions and build own life on some rational principles, to refuse from excessive egoism, combining personal interests with the interests of others and public in generally these ideas were performed in the system of philosophical and legal liberalism, which emerged as a result of the synthesis of individualism and rationality concepts, and became an ideological basis for the modernization of Western civilization.